The Impact of Structure, Process and Output on the Establishment of an Accreditation System in Social Security Hospitals in Tehran - Ebrahim 1, Zahra; Nasiripour 1*, Amir Ashkan; Raeissi 2, Pouran (Shahroud Journal of Medical Sciences, 2017)
Background: The lack of an evaluation mechanism and effective accreditation for hospitals in addition to increasing healthcare costs jeopardizes the overall health of communities. This study was conducted to identify and prioritize factors affecting the establishment of an accreditation system in social security hospitals in Tehran in 2015.Methods: This is a cross-sectional study and participants consisted of academic experts, hospital chiefs, managers, head nurses and supervisors, and staff of quality improvement in departments of social security in hospitals in Tehran City, Iran. Study samples were of 170 participants. A 5-points Likert scale questionnaire, according to the Donabedian model (structure, process, and output), with 24 items, was used. For data analysis, SPSS software version 22 and Pearson correlation coefficient, one-sample t-test and linear regression were used.Results: Out of 170 participants, 49 (28.8%) were male and 121 (71.2%) were female. T-test results showed that all dimensions had a significant effect on the accreditation system (P<0.05). Also, pearson correlation coefficient results showed that all aspects had a significant correlation with each other (P<0.05). In the regression model, R2 showed that 89.6% of changes of the dependent variable could be predicted.Conclusions: The correct implementation of hospital accreditation requires the specific education for personnel so that they can easily understand the accreditation model and standardized processes that need to be established in the hospital.